Evaluasi Saluran Drainase Jalan Pitulua Kecamatan Rante Angin Kota Lasusua Kabupaten Kolaka Utara - Fadhilah, Alfian (Program Studi Teknik Sipil Universitas Bosowa, 2023)
This study aims to determine whether the drainage canal can control/accommodate flood discharge. This research was conducted in the Pitulua Street area, Rante Angin District, Lasusua City and began in October 2021. The type of research is descriptive quantitative case study approach. The object of this research is the drainage channel of Jalan Pitulua, Rante Angin District, Lasusua City. The results of this study note that the drainage channel with an existing capacity of 1.6854 m3/s (right), 1.863 m3/s (left) can accommodate the design flood discharge of 1.511 m3/s (Q2), 1.614 m3/s (Q5) and 1.677 m3/s (Q10)